A hybrid HS-CSS algorithm for simultaneous analysis, design and optimization of trusses via force method - Kaveh, Ali; Khadem Hosseini, Omid (Periodica polytechnica. Civil engineering. Bauingenieurwesen, 2012)
In this paper, a hybrid heuristic method is developed using the harmony search (HS) and charged system search (CSS), called HS-CSS. In this algorithm the use of HS improves the exploitation property of the standard CSS. An energy formulation of the force method is developed and the analysis, design and optimization are performed simultaneously using the standard CSS and HS-CSS. New goal functions are introduced for minimization, and the CSS and the HS-CSS are employed for continuous optimization. An efficient method is introduced using the CSS and HS-CSS for designing structures having members of prescribed stress ratios. Finally, the minimum weight design of truss structures is formulated using the CSS and HS-CSS algorithms and applied to some benchmark problems from literature.